ProJET Car Wash / Salman Ahmad Zamil ... [et al.] - Ahmad Zamil, Salman; Azme, Noormala; Sarib, Mohd. Fakhruddin; Anuar, Nurhidayah; Yaakob, Mohd.Ridzuan; Abd. Aziz, Nabihah (Faculty of Civil Engineering, 2003)
This proposal presents the Business Plan of ProJET Car Wash. Our business will start operating on 2nd January 2004. This business was designed to tackle the urban city's car owners by providing car washing services efficiently and convenient to them. The number of cars is increasing drastically each year due to the need of vehicle and also as a result of the economic growth in the community which is getting better and better. But lack of space and time to wash their car which is essential in car care seems to be the main problem as a lot of them lived in apartment and small residential areas.